Non-high-density lipoprotein cholesterol predicts cardiovascular risk better than remnant cholesterol in patients with type 2 diabetes mellitus - Paul Nsiah; Samuel Acquah; Ansumana Sandy Bockarie; George Adjei; Ebenezer Aniakwaa-Bonsu; Oksana Ryabinina (Frontiers in Cardiovascular Medicine, 2025)
BackgroundCardiovascular disease (CVD) is a leading cause of morbidity in patients with type 2 diabetes mellitus (T2DM). Non-high-density lipoprotein cholesterol (non-HDL-c) and remnant cholesterol (RC) have emerged as promising markers of atherogenic risk, but their comparative predictive performance remains uncertain, particularly in resource-limited settings.ObjectiveThis study evaluated the predictive value of non-HDL-c and RC for atherosclerotic cardiovascular disease (ASCVD) risk and associated inflammatory and metabolic disturbances in T2DM patients.MethodsA cross-sectional study was conducted among 154 T2DM patients attending the outpatient diabetic clinic at the Effia Nkwanta Regional Hospital, Ghana. Non-HDL-c and RC were calculated from fasting lipid profiles. The TyG index was used as a surrogate for insulin resistance. ASCVD risk was assessed using the Framingham risk score. Logistic regression and ROC analysis were performed to assess predictive utility. Subgroup analyses were conducted based on BMI, hypertension, and TyG index.ResultsNon-HDL-C was significantly associated with higher ASCVD risk and elevated hs-CRP and resistin levels, while RC showed weaker, non-significant associations. Non-HDL-c had a higher AUC (0.78 vs. 0.62), sensitivity, and specificity. Nearly half of participants (49.4%) had elevated TyG index (>8.7). Non-HDL-C consistently outperformed RC across subgroups.ConclusionNon-HDL-c is a stronger and more practical predictor of ASCVD risk than RC in T2DM patients, particularly in settings with limited access to advanced lipid testing. Its use alongside the TyG index offers a cost-effective approach for enhancing cardiovascular risk stratification in diabetes care.